Coexistent Congenital Aortic Defects, Aneurysm of Sinus of Valsalva, Atrial Septal Defect and Infective Endocarditis: A case report - Mundo-Sagardía, Jorge A.; Johnson, Charles; Calderón, Rafael; Quintana, Cid (Puerto Rico Health Sciences Journal, 2009)
ABSTRACT. Coarctation of the Aorta is frequently associated with bicuspid aortic valve. This is a risk factor for infective endocarditis. Aneurysm of a sinus of Valsalva is a rare defect with a prevalence of 0.09%. They are associated in 10% of cases with a bicuspid aortic valve and less frequently with coarctation of the aorta and atrial septal defect. It is extremely rare the association of coarctation of the aorta with an atrial septal defect. This is one of the first cases reported in Puerto Rico of an adult patient with coarctation of the aorta in association with a bicuspid aortic valve, a ruptured aneurysm of a sinus of Valsalva and an atrial septal defect. The patient is a 22 year old male with coarctation of the aorta diagnosed since childhood who was admitted at the Cardiovascular Center of Puerto Rico with signs of heart failure due to infective endocarditis secondary to a teeth infection. Upon evaluation with transthoracic and transesophageal echos, he was found to have a coarctation at the aortic isthmus, aortic root dilatation, bicuspid aortic valve with vegetation, severe aortic and tricuspid regurgitation, aneurysm of the non coronary sinus of Valsalva with perforation to the right atrium, biatrial enlargement and a dilated right ventricle. Successful antibiotic treatment of endocarditis was achieved followed by surgical replacement of the aortic valve and ascending aorta with closure of the non coronary sinus of Valsalva was done. An secundum atrial septal defect was found and was also closed. Surgical correction of the coarctation of the aorta was postponed for a future time. The patient had a successful postsurgical recovery and was discharged home with anticoagulation treatment.